2023
DOI: 10.1111/ijfs.16844
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of chemical constituents as a tool for understanding the quality of fruits during development and processing operations

Narpinder Singh,
Deepika Kathuria,
Riya Barthwal
et al.

Abstract: SummaryFruit is a crucial component of our diet, and breeding to produce nutrient‐rich cultivars necessitates a thorough examination of their metabolite composition. Fruit contains hundreds of different chemicals, including both primary and secondary (or specialised) metabolites. The structural diversity of health promoting and sensory attributes imparting metabolites and their complex interactions during fruit growth and developments were uncovered by high‐throughput metabolomics. Both targeted and non‐target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 117 publications
0
5
0
Order By: Relevance
“…Several metabolomics investigations have demonstrated the critical importance of assessing small metabolites in determining food quality. Specifically, the application of GC-MS-based metabolomics is considered an appropriate method for the identification of small molecular metabolites, including acids, phenolic acids, amino acids, and sugars (Singh et al, 2023). In the current study, nine different fatty acids determined by GC-MS analysis are shown in Table 2.…”
Section: Influencing Of Microalgal Biomass and Microalgae-derived Ast...mentioning
confidence: 99%
“…Several metabolomics investigations have demonstrated the critical importance of assessing small metabolites in determining food quality. Specifically, the application of GC-MS-based metabolomics is considered an appropriate method for the identification of small molecular metabolites, including acids, phenolic acids, amino acids, and sugars (Singh et al, 2023). In the current study, nine different fatty acids determined by GC-MS analysis are shown in Table 2.…”
Section: Influencing Of Microalgal Biomass and Microalgae-derived Ast...mentioning
confidence: 99%
“…Cheah et al (2013) suggested that many plant-based products, such as lycopene from tomato and grape seed extract, possess intestinal protective benefits and have been used to produce new pharmaceuticals and nutraceuticals for avoiding inflammatory bowel disease (IBD). Singh et al (2023) provided an extensive and comprehensive review on the various metabolites found in fruits, offering a thorough exploration of the diverse array of compounds present in these natural sources. Besides fruits and vegetables, culinary herbs were also being explored for their rich diversity of phenolic metabolites.…”
Section: Food Phytochemicalsmentioning
confidence: 99%
“…The American Chemical Society journal known as Analytical Chemistry dedicated its cover to foodomics in December 2012 (Garc ıa-Cañas et al, 2012). This interdisciplinary field encompasses genomics, which delves into the composition, functions, and expression outcomes of the genome; transcriptomics, which focuses on understanding gene expression at the RNA level; metagenomics, which examines genetic material from diverse samples; metatranscriptomics, which involves in analysing the comprehensive gene expression profile in the microbiome; proteomics, the study of basic structures, shapes, spatial, and temporal localisation of proteins; and metabolomics, a quantitative investigation of all metabolites to understand their relationship with physiological changes (Bordoni et al, 2014;Cifuentes, 2017;Pan & Barrangou, 2020;Singh et al 2023). This integrative approach enhances our understanding of how food contributes to health promotion, disease prevention, and individual performance improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state fermentation is one such process of biochemical modifications of grain matrix brought by microorganisms and their enzymes to enhance physiochemical properties, digestibility, mineral bioavailability and reduce anti-nutrients (Karovičová & Kohajdova, 2007). During solid-state fermentation, microbes produce a wide variety of chemical compounds that enhance its nutritional property and sensory characteristics and boost the overall quality of the finished product (Singh et al, 2023). Lee et al (2008) employed fermentation to enhance antioxidant properties of black beans and observed an increase in phenol and anthocyanin contents.…”
Section: Introductionmentioning
confidence: 99%